James Baine, His Majesty's Master Wright: Principal Building Works and Contracts. Issue 1 (November 2015) - Newland, Kate
Abstract : James Baine was a wright and merchant burgess of Edinburgh operating in Scotland during the second half of the seventeenth century. This article examines his emergence as a main contractor and master of works, and perhaps even an 'architector', through three case studies: the building of Panmure House, Glamis Castle and Brechin Castle. Baine's career and ultimate bankruptcy also illustrate changes in the way building projects were undertaken and the transference of financial risk from owner to tradesman.